PENGARUH IMPLEMENTASI PEMBELAJARAN PENDIDIKAN PANCASILA BERBASIS KURIKULUM MERDEKA DALAM MEMBENTUK GOOD CITIZEN DI KELAS VIII SMP NEGERI 24 MEDAN - MANURUNG, ANNA MAUDINA; YUNITA , SRI (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2024)
This research aims to determine the influence of the implementation of Pancasila Education learning based on the Merdeka Curriculum implemented by teachers in forming good citizens in class VIII students at SMP Negeri 24 Medan. The research method used in this research is mix methods, a descriptive correlation type of research, with data collection techniques through observation, interviews, and questionnaires. In this study, the population was used, namely all class VIII students, totaling 350 students, and the sample in this study was 15% of the total number of class VIII students, namely 53 students, using the proportionate stratified random sampling technique. Then data analysis is carried out based on data on variables x and y with the hypothesis that if tcount is greater than ttable then the working hypothesis (Ha) is accepted and (Ho) is rejected, conversely if tcount is smaller than ttable then the working hypothesis (Ha) is rejected and (Ho) is accepted . Based on the research results which have been analyzed using the product moment correlation formula, the rcount value is 0.557 which is greater than the rtable value of 0.270 at a significance level of 5% with degrees of freedom (dk) = n-2 (53-2 = 51) so we get ttable = 0.270 , and the results of the "t" test obtained a value of tcount = 4.789 with a value of ttable = 0.270 because tcount ? ttable (4.789 ? 0.270), so the conclusion obtained was that Ha was accepted. This has proven that there is an acceptable influence of the implementation of Pancasila Education learning based on the Independent Curriculum in forming good citizens in class VIII of SMP Negeri 24 Medan. So that the implementation of Pancasila Education learning based on the Merdeka Curriculum is influential and can form civic disposition as a character competency of good citizenship in class VIII of SMP Negeri 24 Medan. ABSTRAKPenelitian ini bertujuan untuk mengetahui bagaimana pengaruh implementasi pembelajaran Pendidikan Pancasila berbasis Kurikulum Merdeka yang diterapkan guru dalam membentuk good citizen siswa kelas VIII SMP Negeri 24 Medan. Metode penelitian yang digunakan dalam penelitian ini adalah mix methods, jenis penelitian deskriptif korelasi, dengan teknik pengumpulan data melalui observasi, wawancara, dan angket/kuisioner. Pada penelitian ini menggunakan populasi yaitu seluruh siswa kelas VIII yang berjumlah 350 siswa serta yang menjadi sampel dalam penelitian ini adalah 15% dari jumlah siswa kelas VIII yaitu sebanyak 53 siswa dengan menggunakan teknik proportionate stratified random sampling. Kemudian dilakukan analisis data berdasarkan data variabel x dan y dengan hipotesis jika thitung lebih besar dari ttabel maka hipotesis kerja (Ha) diterima dan (Ho) ditolak, sebaliknya jika thitung lebih kecil dari ttabel maka hipotesis kerja (Ha) ditolak dan (Ho) diterima. Berdasarkan hasil penelitian yang telah dianalisis menggunakan rumus korelasi product moment diperoleh nilai rhitung sebesar 0,557 lebih besar dari nilai rtabel sebesar 0,270 pada taraf signifikan 5% dengan derajat kebebasan (dk) = n-2 (53-2 = 51) maka diperoleh ttabel = 0,270, dan hasil uji ”t” diperoleh nilai thitung = 4,789 dengan nilai ttabel = 0,270 karena thitung ? ttabel (4,789 ? 0,270), sehingga kesimpulan yang diperoleh yaitu Ha diterima. Hal ini telah membuktikan bahwa ada pengaruh implementasi pembelajaran Pendidikan Pancasila berbasis Kurikulum Merdeka dalam membentuk good citizen di kelas VIII SMP Negeri 24 Medan dapat diterima. Sehingga implementasi pembelajaran Pendidikan Pancasila berbasis Kurikulum Merdeka berpengaruh dan dapat membentuk civic disposition sebagai kompetensi karakter dari good citizen di kelas VIII SMP Negeri 24 Medan.